Math(Please, Please, help)
posted by Hannah .
For f(x) = 2x-3 and g(x)= 2x^2 find,
a) (f + g)(x) = My answer is
2x^2 + 2x - 3. Is this correct?
b) (f - g)(x) How would you do this?
c) (f X g)(2) I do not know what to do since the 2 is there.
Determine whether the graph of the following equation is symmetric with respect to the x-axis, the y-axis, and the origin.
y^2 - x - 49 = 0
For x axis -y^2 - x - 9 = 0 is not the same as the first equation so it is not symmetrical to the x-axis. Correct?
For the y-axis y^2 + x - 49 = 0 is not the same as the first equation so it is not symmetrical to the y-axis. Correct?
For the origin -y^2 + x - 49 = 0 is not the same as the first equation so itis not symmetrical to the origin either. Am I correct?
Nevermind,I did not realize that my question was already answered.
b) the same way you did a) , except ..
2x - 3 - (2x^2) =
(f-g)(x) = - 2x^2+ 2x - 3
c) in this case you multiply,
(fxg)(x) = (2x-3)(2x^2
then fxg(2) = (4-3)(8) = .... (I just replaced the x with 2)